Controlled Polymerization of Phenylacetylenes Using Well‐Defined Rhodium Catalysts. Issue 1 (April 2015) - Sanda, Fumio; Shiotsuki, Masashi; Masuda, Toshio; Kitayama, Tatsuki; Aoshima, Sadahito; Kamigaito, Masami
Summary This article deals with (1) the controlled polymerization of an optically active phenylacetylene (PA) derivative using well defined rhodium (Rh) catalyst, [(nbd)Rh{C(Ph)=CPh2}(PPh3)] and the study on the molecular weight dependence of the chirality (degree of helix formation and predominance of one‐handed helicity) of the formed polymers, (2) examination of the polymer end structures by matrix‐assisted laser desorption/ionization time of flight (MALDI‐TOF) mass spectrometry, (3) development of a novel Rh complex coordinated by a tridentate ligand, and [{nbd‐(CH2)4PPh2}Rh{C(Ph)=CPh2}] and the polymerization of PA in a controlled manner.